The Emerging Importance of Non-HLA Autoantibodies in Kidney Transplant Complications - Cardinal, Héloise (J Am Soc Nephrol, 2017)
Antibodies that are specific to organ donor HLA have been involved in the majority of cases of antibody-mediated rejection in solid organ transplant recipients. However, recent data show that production of non-HLA autoantibodies can occur before transplant in the form of natural autoantibodies. In contrast to HLAs, which are constitutively expressed on the cell surface of the allograft endothelium, autoantigens are usually cryptic. Tissue damage associated with ischemia-reperfusion, vascular injury, and/or rejection creates permissive conditions for the expression of cryptic autoantigens, allowing these autoantibodies to bind antigenic targets and further enhance vascular inflammation and renal dysfunction. Antiperlecan/LG3 antibodies and antiangiotensin II type 1 receptor antibodies have been found before transplant in patients with de novo transplants and portend negative long–term outcome in patients with renal transplants. Here, we review mounting evidence suggesting an important role for autoantibodies to cryptic antigens as novel accelerators of kidney dysfunction and acute or chronic allograft rejection.